Penerapan Metode Failure Mode And Effect Analysis (FMEA) dalam Evaluasi Produk Retur Galon di PT. XYZ: Fokus pada Supplier dan Bagian Yang Paling Rentan - Masudha, Maulidatul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. XYZ is a leading bottled water company that has been operating for a long time. The distribution and recycling process of drinking water gallons is a crucial factor for the sustainability of the production process, requiring strict quality control to ensure that the produced products meet standards and consumer needs. The Failure Mode and Effects Analysis (FMEA) method is used to analyze the potential damage to returned (retur) gallons from various suppliers. From the analysis of 500 returned gallon samples, it was found that supplier F contributed the most damage, with the most dominant type of damage being cracks at the bottom of the gallon, which can cause leaks and a decrease in quality during the distribution process. The damage is prioritized for repair due to its high frequency and impact on the company's operations. The FMEA analysis shows that the main factors causing the damage originate from the suboptimal quality of raw materials, the production process by the supplier, and the handling methods during distribution.